You Can Take it with You! The Returns to Foreign Human Capital of Male Temporary Foreign Workers - Casey Warman (Queen's University, Department of Economics, 2007)
The research on immigration has found falling labor market outcomes of immigrants in many Western countries. In Canada, one of the major causes has been the decline in the returns to foreign work experience. Using the 1991, 1996 and 2001 Canadian Census Master Datafiles and applying both parametric and semiparametric techniques, it is found that unlike recently landed male immigrants, temporary foreign workers have no difficulty transferring their human capital to the Canadian labor market and in particular, they obtain very high returns to their foreign work experience. This is even true for temporary foreign workers from non-traditional backgrounds, a group that has had particular difficulty receiving returns to their foreign work experience for recent immigrant cohorts and now composes the majority of Canada's immigration. It is likely that this premium can be partially attributed to the different selection process that temporary foreign workers and immigrants enter Canada under. While immigrants for the most part are selected by the government, the selection process for temporary foreign workers is driven by employers and employers may be better able to assess the transferability of the worker's foreign human capital.
Keywords: J7; J15; J24; J31; 330; Immigrants; Earnings; Temporary Foreign Workers; Partial linear models; Nonparametric regressions; Canada; Nonpermanent residents; semiparametric; Arbeitsmigranten; Arbeitsmigranten; Humankapital; Lohn; Kanada